Comparative effectiveness of a low-calorie diet combined with acupuncture, cognitive behavioral therapy, meal replacements, or exercise for obesity over different intervention periods: A systematic review and network meta-analysis - Kim, Seo-Young; Shin, In-Soo; Park, Young-Jae (Frontiers in Endocrinology, 2022)
Objective: The aim of this study was to evaluate the comparative effectiveness of a low-calorie diet (LCD) combined with acupuncture, cognitive behavioral therapy (CBT), meal replacements (MR), and exercise on weight loss. Methods: The electronic databases MEDLINE, EMBASE, CENTRAL, CNKI, RISS, and KISS were searched systematically. Randomized controlled trials (RCTs) that directly compared the effect of a low-calorie diet (LCD)-combined acupuncture, CBT, and exercise and an MR-based diet on weight loss with LCD-alone for adults with simple obesity (body mass index [BMI] > 25) published before August 2021 were included in the study. Two investigators extracted and coded the data using a template. Any disagreements between investigators were resolved through discussion. Changes in BMI or weight were transformed to Hedges’ g values with a 95% CI, and network meta-analyses using a Bayesian random-effects model were conducted. Results: A total of thirty-two trials involving 3,364 patients were finally included in the study. The effect sizes of four interventions were medium, in the order of acupuncture (Hedges’ g = 0.48, 95% CI = 0.25 - 0.71), CBT (Hedges’ g = 0.42, 95% CI = 0.20 - 0.63), MR (Hedges’ g = 0.32, 95% CI = 0.19 - 0.45), and exercise (Hedges’ g = 0.27, 95% CI = 0.06 - 0.46). In terms of intervention period, acupuncture was effective in the short period (≤ 12 weeks, Hedges’ g = 0.39, 95% CI = 0.12 - 0.67) and the long period (>12 weeks, Hedges’ g = 0.89, 95% CI = 0.37 - 1.40), whereas CBT (Hedges’ g = 0.51, 95% CI = 0.26 - 0.76) and exercise (Hedges’ g = 0.37, 95% CI = 0.12 - 0.59) were effective only in the long period. MR was effective only in the short period (Hedges’ g = 0.35, 95% CI = 0.18 - 0.53). Conclusions: This study suggests that acupuncture, CBT, MR, and exercise for simple obesity show a medium effect size, and their effectiveness differs according to the intervention period.